Efektifitas Peningkatan Minat Baca Melalui Permainan Menyusun Kata pada Anak Usia Dini - Septiani Hapidah; Dian Riskiana Putri (Concept: Journal of Social Humanities and Education, 2024)
This research was conducted on Tuesday, June 11 2024. This research is carried out using qualitative research methos, namely with data collection tehniques throught obsevation, interviews and documentation. This research was condeducated at TA Sanggar Anak Alam with a total 0f 29 subject of TA children large and small. And interviewed 4 facilitators and 1 parent. As for the result of tgis study, after playing words, children experience an increase in intersest in reading, not only that children are also stimulated to learn to write.